2019
DOI: 10.1111/apt.15140
|View full text |Cite
|
Sign up to set email alerts
|

Volatile organic compounds emitted from faeces as a biomarker for colorectal cancer

Abstract: Summary Background Colorectal cancer remains a leading cause of mortality and morbidity. The UK Bowel Cancer Screening Programme (BCSP) has demonstrated that detection of colorectal cancer at an earlier stage and identification of advanced pre‐malignant adenomas reduces mortality and morbidity. Aim To assess the utility of volatile organic compounds as a biomarker for colorectal neoplasia. Methods Faeces were collected from symptomatic patients and people participating in the UK BCSP, prior to colonoscopy. Hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 31 publications
4
59
0
Order By: Relevance
“…We welcome the interest expressed by Leong et al in our work looking at metabolomics biomarkers for gastrointestinal disease . We have previously reported the volatile organic compounds emitted from faecal samples in patients with irritable bowel syndrome, Crohn's disease, ulcerative colitis and asymptomatic controls using headspace gas chromatography mass spectrometry, and also using a gas chromatography‐sensor system .…”
supporting
confidence: 91%
See 1 more Smart Citation
“…We welcome the interest expressed by Leong et al in our work looking at metabolomics biomarkers for gastrointestinal disease . We have previously reported the volatile organic compounds emitted from faecal samples in patients with irritable bowel syndrome, Crohn's disease, ulcerative colitis and asymptomatic controls using headspace gas chromatography mass spectrometry, and also using a gas chromatography‐sensor system .…”
supporting
confidence: 91%
“…The editorial accompanies our latest study which has reported the association between a small group of faecal volatile organic compounds and the presence of colorectal adenocarcinoma . Propan‐2‐ol (also known as isopropanol) was significantly more abundant in the cancer samples than controls ( P < 0.0001, q = 0.004).…”
mentioning
confidence: 99%
“…The selected model provided correct classification of 14 patients with polyps over 15 for the group of patients with colorectal cancer, with a sensitivity of 93.3%. Group with polyps were distinguished as markedly pathological [ 48 ].…”
Section: Studies On Colorectal Cancer Metabolic Biomarkersmentioning
confidence: 99%
“…In gastrointestinal diseases, faecal and urinary samples are ideal sources of metabolic signatures of divergent pathogenic pathways; the noninvasive nature of their collection makes them fitting for novel diagnostics. Two recent publications in AP&T aimed to identify molecules that accurately diagnose gastrointestinal diseases based on metabolic profiling.…”
mentioning
confidence: 99%
“…Using Headspace GCMS to define profiles of volatile organic compounds (VOCs) in faeces, Bond et al were able to accurately differentiate patients with colorectal adenocarcinoma from controls by summation of three compounds (AUROC 0.73). Propan‐2‐ol was the strongest single biomarker with an AUROC to predict adenocarcinoma of 0.76.…”
mentioning
confidence: 99%